PEMBUKTIAN NEGATIF DALAM PERSIDANGAN PERKARA TINDAK PIDANA ILLEGAL FISHING TANPA HADIRNYA TERDAKWA DALAM PUTUSAN NOMOR 13/Pid.Sus- PRK/2021/PN.Bit. - Agung Ega Prayoga; Bambang Santoso (Sebelas Maret University, 2025)
This study aims to determine the application of the negative evidentiary system in proving the crime of illegal fishing in verdict Number 13/Pid.Sus-PRK/2021/PN.Bit. As a legal research, this research is a normative research, focusing on studying primary and secondary legal materials. The nature of the research is prescriptive, research that aims to provide suggestions or things that should be done, especially concerning what the judge should do in applying the negative evidentiary system to illegal fishing cases tried in absentia. The research approach used is the case approach, namely examining the judge's considerations in sentencing illegal fishing cases. The technique of collecting legal materials with literature studies, consisting of primary and secondary legal materials. Analysis of legal materials is carried out using the syllogistic deduction technique.Based on the results of the study, it is known that the application of the negative evidentiary system in proving the crime of illegal fishing in verdict Number 13/Pid.Sus-RK/2021/PN.Bit, by the judge has fulfilled the provisions of Article 183 of the Criminal Procedure Code. In the trial, the judge obtained 3 (three) pieces of evidence in the form of witness testimony, expert statements and the defendant's statement which gave rise to the judge's conviction. In addition, the judge also considered that the defendant was a person who was capable of being responsible because there was no reason to eliminate the criminal offense, either a reason for forgiveness or justification.